Respon Siswa dalam Menyelesaikan Soal Literasi Matematika pada Konteks Bangka Belitung - Rajab Vebrian; Yudi Yunika Putra; Sari Saraswati (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2022)
Mathematical literacy has an important role in helping students understand the use of mathematics in everyday life. The purpose of this study was to determine student responses in solving mathematical literacy problems. Student responses are answers to questions related to attitudes and feelings after completing mathematical literacy questions. This study used descriptive qualitative method. Data collection techniques in the form of questionnaires and interviews. The research subjects were 22 students of class X. This research instrument used a questionnaire sheet and an interview sheet. Interviews were conducted on 3 subjects who have high, medium, and low abilities. Questionnaire and interview data were analyzed qualitatively. The results showed that the average student response after being given a mathematical literacy question reached 55% with a good category. Students feel interested and enthusiastic about working on literacy questions, math literacy questions are different from the questions that are usually done in class, want literacy questions to be applied in everyday learning, even though students are not yet able and accustomed to working on mathematical literacy questions.